Exploring the role of gut microbiota dysbiosis in gout pathogenesis: a systematic review - Shirvani-Rad, Salman; Khatibzade-Nasari, Niloufar; Ejtahed, Hanieh-Sadat; Larijani, Bagher (Frontiers in Medicine, 2023)
Objectives: Gut dysbiosis is believed to be one of the several mechanisms that are involved in the pathogenesis of gout. This systematic review aimed to summarize the role of gut dysbiosis in gout disease and uncover the underlying mechanisms. Methods: A comprehensive search was conducted on PubMed, Web of Science, and Scopus databases up to October 2021. Animal studies and human observational studies, including case-control, cross-sectional, and cohort studies assessing the association between gut microbiota composition and gout were included. The quality of included studies has been evaluated using the Newcastle–Ottawa Quality Assessment scale (NOS) and the SYRCLE's risk of bias tool. Results: Initially, we found 274 studies among which 15 studies were included in this systematic review. Of them, 10 studies were conducted on humans and 5 studies were conducted on animals. Increased abundance of Alistipes and decreased abundance of Enterobacteriaceae alters purine metabolism, thereby aggravating gout condition. Moreover, a higher abundance of Phascolarctobacterium and Bacteroides in gout modulates enzymatic activity in purine metabolism. Butyrate-producing bacteria such as Faecalibacterium, prausnitzii, Oscillibacter, Butyricicoccus, and Bifidobacterium have higher abundance in healthy controls compared to gout patients, suggesting the anti-inflammatory and anti-microbial role of short-chain fatty acids (SCFAs). Lipopolysaccharides (LPS)-releasing bacteria, such as Enterobacteriaceae, Prevotella, and Bacteroides, are also involved in the pathogenesis of gout disease by stimulating the innate immune system. Conclusion: Exploring the role of gut dysbiosis in gout and the underlying mechanisms can help develop microbiota-modulating therapies for gout.